2004
DOI: 10.1002/bjs.4629
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of controlled trials assessing spinal cord stimulation for inoperable critical leg ischaemia

Abstract: The addition of SCS to standard conservative treatment improves limb salvage, ischaemic pain and the general clinical situation in patients with inoperable chronic critical leg ischaemia. These benefits should be weighed against the cost and the (minor) complications associated with the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 25 publications
1
47
0
7
Order By: Relevance
“…The authors observed a stronger trend towards a better rate of amputation-free salvage in the subgroup of patients selected by initial tcpO 2 measurements. 9 Predrini and Magnoni reviewed the efficacy of SCS in patients with untreatable CLI and found that pain relief, ulcer healing, and limb salvage were greater in nondiabetic patients, in diabetic patients without autonomic neuropathy, and in patients with rest pain or ulcer more often than in patients with gangrene. 7 The Cochrane review of SCS for nonreconstructable CLI found that limb salvage after 12 months was significantly higher in patients with the device.…”
Section: Scs and The Arterial Microcirculationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed a stronger trend towards a better rate of amputation-free salvage in the subgroup of patients selected by initial tcpO 2 measurements. 9 Predrini and Magnoni reviewed the efficacy of SCS in patients with untreatable CLI and found that pain relief, ulcer healing, and limb salvage were greater in nondiabetic patients, in diabetic patients without autonomic neuropathy, and in patients with rest pain or ulcer more often than in patients with gangrene. 7 The Cochrane review of SCS for nonreconstructable CLI found that limb salvage after 12 months was significantly higher in patients with the device.…”
Section: Scs and The Arterial Microcirculationmentioning
confidence: 99%
“…3,8 Briefly, spinal cord stimulation requires the insertion of electrodes into the epidural space, with the electrodes connected to an impulse generator. 9 To treat lower-extremity pain in patients with CLI, 4 to 8 electrodes are generally placed in the epidural space between the thoracic 8 and 11 level through a paralaminar level 1 or 2 lumbar puncture. 4,10 The electrodes are usually centered in the spinal canal or directed off-center, depending on the location of the limb with the most significant symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With appropriately selected patients at centers with interdisciplinary expertise, the trial-to-implant conversion rates can be quite encouraging: in the 65%-80% range for various diagnoses, 15 although from a nationwide perspective, the actual conversion rate remains less encouraging at approximately 41%. 7 The utility of this technology has been demonstrated in prospective randomized and observational studies, and in systematic literature reviews for various pathologies, including PPNP after structurally corrective lumbar spinal surgery, 6 complex regional pain syndrome, 27 chronic inoperable limb ischemia, 31 treatment-refractory angina, 28 and painful diabetic neuropathy. 3 Despite its proven efficacy for the PPNP population, there have been a few small studies that reported on the risk experienced by patients undergoing such intervention specifically in the context of managing neuropathic pain after lumbar spinal surgery, and whether those rates of complication are variable by surgical technique.…”
mentioning
confidence: 99%
“…Eine Reihe von randomisierten kontrollierten Studien beschrieb zwar einen positiven Effekt auf die Schmerzen durch die SCS, aber unterschiedlichen Ergebnisse bezüglich der Erhaltung der Extremitäten [1,19]. Ein Cochrane Review [45] und eine Metaanalyse [44] mit Pooling der Daten konnten jedoch einen signifikanten Effekt auch hinsichtlich des Extremitätenerhalts nach 12 Monaten nachweisen. Die NNT betrug 9 (95% Konfidenzint.…”
Section: Epidurale Rückenmarkstimulation Bei Peripherer Arterieller Vunclassified